MODREN METHODS OF USING PLASTINATION IN TEACHING ANATOMY. Short review - Alaa Sawad et al (Basrah Journal of Veterinary Research)
Plastination is an anatomical preservation process Samples by precise technique of compulsory impregnation by processable polymer such as silicone, epoxy or polyester Resins that have wide usages in the medical field. The tissue reservation technology was developed by Dr. Gunther von Hagens in 1978. By this method we can store and preserve the body and wipes it for the aim of learning. Current there are new and various kinds of plastination used the learning and in museums. This review aims to explain the main steps of soft plastination used either techniques or methods and their implementation for the medical and veterinary educations.